A Study on the flow around a tall building with "rotating part" - 458947 Sia, Bee Yin (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Aeronautical) - Universiti Teknologi Malaysia, 2003